Wide locking range frequency tripler based on a dual‐band VCO. Issue 21 (1st September 2020) - Zhou, H.F.; Shum, K.M.; Chan, C.H.
Abstract : A wide locking range (LR) injection locked frequency tripler (ILFT) based on a dual‐band voltage controlled oscillator (VCO) is proposed in this Letter. By rationally designing the transformer parameters, the VCO can easily realise the adjacent dual‐band operating characteristics. The ILFT has dual LRs which can easily overlap each other at a fixed bias. A subharmonic signal is also injected through the transformer for frequency locking. A wide LR of 27.1% from 69 to 90.6 GHz at an injection power of 0 dBm is achieved whereas the tripler only consumes 5.88 mW under a 0.6 V supply voltage.